Double-Sided LCC V2G Inductive Link With Four-Quadrant Control for an EV SAE J2954-Compliant Charger - Inmaculada Casaucao; Alicia Trivino (IEEE Access)
Electric vehicles (EVs) have a high impact on power systems, since the demand peaks they generate can cause instabilities in the electricity grid. One of the technologies that are proposed to alleviate this impact is Vehicle-to-Grid (V2G) strategies, which could be implemented in conductive charger and in advanced equipment such as wireless charging. V2G combined with adjustable power levels (in the charging and discharging processes) adds flexibility to the grid. The aim of this paper is the definition of a V2G control wireless system working in V2G 4-quadrants, where any combination of active and reactive power is possible. In this way, the EVs with wireless charging can participate in multiple ancillary services, beyond the traditional approach to comply with power quality requirements. The main contribution of this work is that a SAE J2954-compliant EV charger has been considered, where it is included a double-sided LCC compensation topology due to its popularity. To do so, analytical studies, simulations and experimental validations up to 500 W have been carried out. The final results highlight the feasibility of this system in eight operation modes, achieving an overall efficiency higher than $90~%$ .